The importance of the architectural ensemble of the metropolitans residence of Bukovina and Dalmatia in the formation tourist image of Chernivtsi - Andrusiak, Natalia; Anipko, Nataliia (Human Geography Journal, 2022)
The role architectural ensemble of Metropolitans Residence of Bukovina and Dalmatia in the formation of the Chernivtsi tourist image was analyzed in the article. Metropolitans Residence of Bukovina and Dalmatia is one of the the most popular tourist sites in Ukraine. The quantitative indicators of the monument’s attendance by tourists from Ukraine and abroad in the period from 2018 to 2021 are analyzed. Ways and measures have been identified that would increase the number of visitors to the Metropolitans Residence of Bukovina and Dalmatia. One of the four aspects of the tourist image of the city was identified – the real image of Chernivtsi. For this purpose, a questionnaire was developed and a questionnaire was conducted among tourists from different regions of Ukraine who visited the city of Chernivtsi and the Residence of the Metropolitans of  Bukovina and Dalmatia.The purpose of the survey was to determine the impressions of tourists after visiting the monument and to find out, in their opinion, its role in forming a positive image of the city of Chernivtsi. 2,500 people of different ages took part in the survey. Questionnaire survey (11 questions) was conducted by online e-mail, google-forms and by survey on social networks.The survey revealed the real image of Chernivtsi and the role of the architectural ensemble of the Metropolitans Residence in its formation. The answers of the respondents showed the problematic moments and reasons why the real image of Chernivtsi is still far from optimal. Therefore, the results of the study can be taken into account in the formation of the optimal image of the city of Chernivtsi and future research in this direction.